Implementasi Program Bantuan Langsung Tunai (BLT) Bagi Masyarakat Miskin di Nagari Batang Arah Tapan - Azizah, Kharisma Nur; Nuzuli, Ahmad Khairul; Oktaviana, Winda (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
The purpose of this study was to determine the implementation of the Direct Cash Assistance (BLT) program in Nagari Batang Arah Tapan. The method used in this study is a descriptive research method with a qualitative approach to analyze the implementation of the cash transfer program in Nagari Batang Arah Tapan. The author collected various data regarding the BLT program which was carried out through literature review and interviews with the community and local nagari officials. Determination of the sample is done by using the unit of analysis method. The results of the research show that the implementation of the direct cash assistance program for the poor in Nagari Batang Arah Tapan has been implemented quite well. This can be seen from various measuring aspects, including aspects of policy standards and targets, resources, characteristics of the implementing agency, and the disposition of the implementer